PENGARUH UMUR OBLIGASI, TINGKAT SUKU BUNGA, DAN INFLASI PADA IMBAL HASIL OBLIGASI PEMERINTAH DI BEI - Yuliawati, Devi; Suarjaya, A.A. Gede (E-Jurnal Manajemen; Vol 6 No 11 (2017), 2017)
ABSTRACT Bond yields represent income received by bondholders and one of the benchmarks used by investors to monitor the development of the government bond market. This study aims to determine the effect of the maturity, interest rates, and inflation on the yield of government bonds on IDX. This research was conducted at IDX. In this research is secondary data obtained from IDX, KSEI, IBPA, BI, and TICMI. Population and sample in this research the data is government bond with Fixed Rate (FR) code which recorded and active in IDX year 2012-2015 amounted to 39 government bonds, using saturated sampling method. The analysis technique applied was multiple linear regressions. Based on the analysis, the conclusion are maturity have an insignificant effect on bond yields. Interest rates have positive and significant effect on bond yields. Inflation have an insignificant effect on bond yields. Keywords : bond yield, maturity, interest rate and inflation .